The impact of TÜSİAD on the European Union relations of Turkey (1995-2005) - Soysal, Emre. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2007., 2007)
This thesis examines TÜSİAD and its impact on Turkey-EU relations as a civil society organization, which is an actor of foreign policy for a decade starting from the mid 90s. The changing foreign political issues in the context of the changing international system after the collapse of the Cold War system is analyzed together with the changing and increasing roles of the civil society organizations during the period. The thesis also presents a historical background for the development of the relations between the Turkish state and businessmen. Based on the theoretical and historical background summarized above, the thesis analyzes the organizational characteristics of TÜSİAD, its membership policy and its foundation principles. With the explained organizational structure, the activities of TÜSİAD, on the path to the EU are described in detail and its impacts both abroad and inside the country are presented within the text. Moreover, the text includes economic data that has given the motive to TÜSİAD to be so active for the membership of Turkey to the EU, based on the growth and foreign trade data.